The impact of COVID-19 on e-commerce: a cross-national analysis of policy implications - Cheong, Jia Qi; Tsen, Wong Hock; Abdul Karim, Samsul Ariffin; Cheah, Jeffrey S. S. (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
The field of e-commerce research has evolved over recent decades, but the coronavirus disease 2019 (COVID-19) pandemic significantly accelerated its prominence, as evidenced by extensive literature. The pandemic underscored the pivotal role of e-commerce in driving the digital transformation of the global economy. However, there remains a lack of comprehensive reviews in this area, particularly comparative analyses of how different countries leveraged e-commerce to navigate the pandemic’s challenges. This paper addresses this gap by examining the literature on e-commerce adoption and its implications during COVID-19, focusing on select countries, including China, Malaysia, and several European nations. The case of China, as a major economic power in Asia, offers particularly valuable insights.